A computational framework for constitutive modelling. (15th July 2017) - Gori, Lapo; Penna, Samuel Silva; Pitangueira, Roque Luiz da Silva
Abstract: The field of computational constitutive modelling for engineering applications is an active research tread in academia. New advanced models and formulations are constantly proposed. However, when dealing with implementation aspects, often the main concern is to provide a minimal environment to show a certain model and its applications, with implementations made from scratch. Though advanced, usually such implementations lack of generality and are well-suited for a certain numerical method while not compatible with other ones, making it difficult to reuse the code in other contexts. The Object-Oriented Paradigm (OOP) to programming have been widely applied in the last years for the realization of numerous academic numerical simulation softwares, due to its fundamental properties of abstraction, inheritance and polymorphism that allow the creation of programs well-suited for an easy collaboration between developers with expertise in different fields of engineering and mechanics. As showed in this paper, the same properties can be effectively extended also to the constitutive aspects of a model. The application of the OOP to the constitutive modelling of a wide range of materials of engineering interest is investigated, aiming to the creation of a computational framework for constitutive models that is fully independent on the other components of a code and easy to expand.